Scientific Visibility of researchers in Work Group-4 of the National Association of Research and Post-Graduate in Information Science through citation and co-citation - Alves, Bruno Henrique (Faculdade de Filosofia e Ciências, 2020)
This research aims to analyze the researchers with the greatest visibility who contributed to the development of the Work Group-4 theme: Information and Knowledge Management, of the National Association of Research and Post-Graduation in Information Science through the analysis of citation and co-citation in the period from 2013 to 2019. Data collection was based on a summary consisting of 109 studies, without self-citation. In this set, a total of 2,604 references were found. Finally, a square matrix of 74X74 researchers was built, and the Ucinet software was used to generate the co-citation network. As a result, of this group of researchers, 46 (62.2%) were linked to Brazil. The highest co-citations frequencies are found between Davenport, T. and Prusak, L. (34 co-citations); Nonaka, I. and Takeuchi, H. (28 co-citations), among others. As final considerations, citation analysis can be used to identify the research front, and co-citation analysis is used to identify thematic similarity.